Hubungan Self-Efficacy Dengan Stres Akademik Pada Mahasiswa S1 Biologi FMIPA Universitas Pattimura Dalam Proses Penyusunan Skripsi - Pangemanan, Victory O; Manery, Dodikrisno E; Ukratalo, Abdul M; Nanere, Bill E; Embisa, Yushar A; Assagaf, Abdur Rahman (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
The process of preparing a thesis is a crucial stage in the academic journey of undergraduate Biology students. At this stage, students are faced with complex and demanding tasks, requiring effective self-regulation skills and resilience to academic pressure. This research aims to investigate the relationship between self-efficacy and academic stress among undergraduate Biology students at the Faculty of Mathematics and Natural Sciences, Pattimura University, during the thesis preparation process. This research employs a quantitative approach with data collection through questionnaires distributed to undergraduate Biology students. Statistical analyses, such as correlation, will be utilized to assess the relationship between self-efficacy and academic stress. The research findings reveal that the most common level of self-efficacy falls within the moderate category. Meanwhile, the categorization of academic stress levels indicates that the majority of respondents, comprising 19 individuals (44.2%), experience mild stress. Statistical analysis unveils a significant relationship between the level of self-efficacy and academic stress among students.